Spectroscopic electron temperature measurement in methane/helium plasma during diamond-like carbon coating - Artit Chingsungnoen" (Science Faculty of Chiang Mai University, 2019)
The electron temperature () was extracted from the capacitively-coupled radio frequency (CCRF) plasma reactor by the spectral line intensity ratio method. The measured intensity ratio of 587.6/706.5 nm from CH4/He plasma was used to calculate the electron temperature under the steady state corona (SSC) approximation. Results were in good agreement with Langmuir probe measurement. This analysis method was then used to determine the electron temperature profile of CH4/He plasma. The increase in power density from ~980 to ~1715 mW/cm2 resulted in a decrease in the electron temperature from ~0.93 eV to ~0.65 eV. The highest electron temperature appeared at the discharge radial center and ~4 mm from the RF powered electrode. From the radial electron temperature measurement, the temperature gradient inside the discharge region tended to decrease with the increase in power density, while in the axial direction, the electron temperature changed sharply near the powered electrode.